Sex Differences in the Medical Utilization for Ischemic Heart Disease Among Newly Diagnosed Hypertensive Korean Patients (P04-170-19) - Shin, Jiae (Curr Dev Nutr, 2019)
OBJECTIVES: This study aimed to investigate sex differences in the medical utilization for ischemic heart disease (IHD) among newly diagnosed hypertensive patients using a cohort data of South Korea. METHODS: We analyzed the National Sample Cohort version 2.0 of the National Health Insurance Service. Newly diagnosed hypertensive patients aged 40–84 were extracted from the baseline population, who received health examinations during 2003–2006 without pre-existing type 2 diabetes or circulatory diseases. Propensity score was applied to match men to women with the same ratio of body mass index (BMI) and fasting blood glucose (FBG) among the patients. Men and women (each 10, 110) were selected for analyses and followed until the end of 2015. Person-year was defined as the period from the diagnosis of hypertension to the incidence of IHD. Associations between IHD and the medical care utilization such as the mean of medical care visit, the mean medical cost, and the type and the location of medical care providers were investigated using Cox proportional hazard model. Hazard ratios (HR) of IHD according to medical care utilization were adjusted for age, income, BMI, FBG, smoking, and alcohol consumption. RESULTS: Incidence rates (per 1000 person-years) of IHD were 43.1 in men and 43.0 in women. The mean follow-up period was 5.2 person-years. The HRs of IHD were significantly higher in the subjects with a high mean medical cost (T3) (men, HR = 1.39, 95% CI 1.25–1.54; women, HR = 1.33, 95% CI 1.20–1.48) than in those with a low mean medical cost (T1). However, the subjects visiting medical care providers more (T3) had lower HRs than those visiting less (T1) (men, HR = 0.80, 95% CI 0.72–0.89; women, HR = 0.79, 95% CI 0.71–0.88). CONCLUSIONS: Hypertensive patients in Korea showed an increased risk of IHD when they paid medical cost more and visited medical care less per person-year in both men and women. FUNDING SOURCES: This research was supported by Support Program for Women in Science, Engineering and Technology through the National Research Foundation of Korea funded by the Korea government (MSIT). (No.2016H1C3A1903202). SUPPORTING TABLES, IMAGES AND/OR GRAPHS: